The Impact of Trade Liberalization on Informal Employment in Costa Rica’s Manufacturing Sector During the Period 1996–2009 - Delgado Jiménez, Francisco (2012)
This article analyzes the impact of trade liberalization on informal employment in Costa Rica’s manufacturing sector during the period 1996–2009. Although trade liberalization affects firms that produce goods solely for the domestic market differently from those that focus on exporting their production, the effect of exporting firms that generate formal jobs is expected to predominate; therefore, the hypothesis is that an increase in trade liberalization leads to a reduction in informality. The study found no statistical evidence to suggest that the process of economic liberalization Costa Rica underwent during that period had a positive or negative effect on employment in the informal sector of the economy within the manufacturing industry.